2003
DOI: 10.1007/s00216-002-1726-8
|View full text |Cite
|
Sign up to set email alerts
|

Study of the acid–base properties of fulvic acid-like substances extracted from senescent leaves of eucalyptus and oak

Abstract: The acid-base properties of two fulvic acids (FA) extracted from senescent leaves of eucalyptus and oak were characterized by carrying out potentiometric titrations at two FA concentrations and four ionic strengths (0.005 M <[KNO(3)] <1.0 M). Experimental data were analyzed by means of the master curve approach, which includes an electrostatic spherical double layer model, and the Langmuir-Freundlich isotherm was used to fit the data. The contribution of the electrostatic effect to the proton binding reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
2
0
0
Order By: Relevance
“…1 it is apparent that the negative charge on humic acid increased as pH increased due to the dissociation of the acidic functional groups of humic acid and this is in agreement with relative results already reported in the literature [27,28,[35][36][37][38][39]. The negative charge on GHA (200, 100, and 50 mg L À1 ) at pH 3.5 was equal to 1 = 4 of the developed negative charge at pH 10.…”
Section: Proton Bindingsupporting
confidence: 91%
“…1 it is apparent that the negative charge on humic acid increased as pH increased due to the dissociation of the acidic functional groups of humic acid and this is in agreement with relative results already reported in the literature [27,28,[35][36][37][38][39]. The negative charge on GHA (200, 100, and 50 mg L À1 ) at pH 3.5 was equal to 1 = 4 of the developed negative charge at pH 10.…”
Section: Proton Bindingsupporting
confidence: 91%
“…Comparison of the different types of vegetation shows that in the FA extracted from the surface horizon of both AM and GR soils, the lowest values of the C/N atomic ratio correspond to Eucalyptus spp., in accordance with Antelo et al (2003), who found a greater content of N in the fulvic-like acids extracted from senescent leaves of Quercus robur than in fulvic-like acids extracted from senescent leaves of Eucalyptus globulus.…”
Section: Chemical Composition Of the Humic Substancessupporting
confidence: 89%